Acculturation and Linguistic Tensions as Predictors of Quebec Francophone and Anglophone Desire for Internal Migration in Canada. (March 2018) - Sioufi, Rana; Bourhis, Richard Y.
Using the acculturation and ethnolinguistic vitality frameworks, this study examined economic prospects and linguistic tensions as factors accounting for willingness to stay in Quebec or leave to the rest of Canada. Questionnaires were completed by Quebec Francophone (QF; n = 234) and Quebec Anglophone (QA; n = 205) undergraduates attending French- and English-medium universities in Montreal, respectively. Results showed that, compared with QFs, QA minority students were more willing to leave Quebec. For QFs, willingness to move to the rest of Canada was predicted mainly by pull factors including better economic prospects and joining a partner. Though QFs and QAs identified similar pull factors, the following push factors were more important for QAs: avoiding linguistic tensions, being victim of collective discrimination, perceiving English–French relations as zero-sum, and endorsing the separation acculturation orientation. Results show the importance of linguistic tensions as a factor predicting QAs' willingness to leave their province of origin.